Medicinally İmportant Representatives Of The Brassicaceae Burnett. Family Cultivated İn Agriculture And Their Effect On The Neonatal Development Process - M. Aliyeva, Afag (Journal of Neonatal Surgery, 2025)
The article discusses the medicinally significant representatives of the Brassicaceae Burnett family cultivated in agricultural practices. These include Armoracia rusticana (Gaertn.) C.A. Mey. & Scherb. from the genus Armoracia (Gaertn.) C.A. Mey. & Scherb., Brassica oleracea L. from the genus Brassica L., Lepidium sativum L. from the genus Lepidium L., and Raphanus sativus L. from the genus Raphanus L. The article provides information about the biochemical composition of these plants relevant to the neonatal developmental period. During the neonatal period, the brain develops intensively, and the immune system is weak. The paper outlines the vitamins, minerals, and other substances in these plants that are essential for normal brain development and immune strengthening. Additionally, the article highlights the importance of these plants in other fields and their roles in the treatment of various diseases.